Walking the Last Mile : Operationalization of Albania’s Authorized Economic Operators Program - Kastrati, Pranvera; Meko, Mirela; Saragiotis, Periklis (International Finance Corporation, Washington, DC, 2017)
Albania’s authorized economic operators (AEO) program is not yet operational, even though the country has adopted the necessary European Union (EU) legal and regulatory frameworks. This smart lesson outlines shortcomings in the adoption of AEO provisions under the European community customs code (CCC) as well as the obstacles the national government has faced putting in place the complementary reform measures necessary to ensure practical effectiveness. Lessons learned from the Albanian experience may be instructive for other countries in the central European free trade agreement region as they look to operationalize their AEO programs without diverting from AEO guidelines as set out in the EU acquis.